Kajian Estetika Interior Restoran Boncafe Di Jalan Pregolan Surabaya - Fanuel W., Yemima (Intra, 2014)
Boncafe Pregolan restaurant is a restaurant in Surabaya located at Pregolan Street 2, Tegal sari, Central Surabaya. Boncafe Pregolan restaurant built in 2007. The interior of Boncafe Pregolan restaurant is divided into several rooms, main entrance area, main dining area I, main dining area II, smoking dining area, and terrace dining. The aesthetic ofÂ  interior Boncafe Pregolan restaurant is interesting to be analyzed, because of the interiorâs plays inside. The design principles implemented to the interior elements and their composition, also the furnishing. the interior design shows that there is not simply designed shows the existance of aesthetic process inside. The interior of Boncafe Pregolan restaurant is adequate to be analyzed from its aesthetic using the design elements and principles. The analysis method used is descriptive qualitative method by comparing field data with qualified literature data.Based on the analysis of its interior building elements and furnishing, the result shows that in interior of Boncafe restaurant , the use of square form, rectangle form, and the line elements dominates the space, the abstract form is the accent form for the space. Repetition of the form takes place to unified the space hamoniously. The use of the color for the entire space is a safe color composition, namely neutral colors, natural colors, red, yellow, blue as accent color. The use of neutral colors and natural colors are easier to combined and easier to be unified without any space chaos. The most dominant design principle is the harmonious of the space seen from visual rythyme of the interior building elements and furnishing. In Monroe Beardsley theory, aesthetic object has a whole unity that the object is perfectly arranged. The unity is achieved by the implementation of design principles, there are repetitions of the interior elements. Secondly, complexity or interpreted as harmony which shown from the windows pattern of main dining area II and smoking dining area. Thirdly, intensity or interpreted as focal point and not monotone. The stone wall stands as the focal point of the whole area and the use of alternation repetision and accent color on neutral and natural color, make non monotonic design. As a whole, the aesthetic of Boncafe Pregolan restaurant analyzed from design elements and principles achieve its aesthetic.